Effects of various vitamin and trace elements of minerals supplementation in lamb diets on fattening performance, blood plasma levels, wool characteristics and nutrient digestibility - Halit İmik; Behiç Coşkun; Melik Aytaç (Eurasian Journal of Veterinary Sciences)
In this study. it was aimed to search the effect of vitamin and trace minerals on the faltening performance, blood plasma, wool quality, and digestibility in lambs. Thirty five. about 2.5 months-old, Akkaraman lambs were used for 56 days. The search was conducted with 5 different groups. Vitamin and mineral premix were not added to the diets of first group, commercial levef of vitamin premix were added to the diets of second group (V), commercial level of mineral premix were added to third group (M), both vitamin and mineral premixes were added together to the diets of forth group (VM), half commercial level of both premixes were added to the diets of fifth group (VM/2). The temperatures varied from 24 to 36 C during the study. In K, V, M, VM and VM/2 groups average daily live weight gains were 241, 271, 368, 350 and 361 gram respectively. The groups to which mineral premix were added gained more weight than the other groups significantly (P<0.05). After shearing thickness in the samples obtained from HİP area were 22.69, 27.71, 27.56, 27.60 and 27.30 ( respectively. In addition dirty and clean wool weights, heights and on-dulation rate were determined. At the end of fattening period, the levels of vitamin A in blood sera samples were 81.30, 100.19, 100.96, 80.54 and 81.52 d/dl; 175.21, 198.93,269.46,236.43 and 251.39 d/dl for Zn; 172.68, 152.50, 172.68, 152.50, 127.00, 127.14 and 107.22 d/dl for Cu respectively. As a result, adding the mineral premixes in the lamb fattening diets caused to increase in body weight and tend to increased in thickness ol the wool.